Assessment of wastewater temperature and its relationship with turbidity - Mandal, Harashit Kumar (Recent Research in Science and Technology, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--> Turbidity consists of suspended material in water, causing cloudy appearance. This cloudy appearance caused by scattering and absorption of light by these particles. The suspended matter may be inorganic or organic. Generally the small size of particles prevents rapid settling of the material. Turbidity can provide food and shelter for pathogens. Solids are present in water in three main forms: suspended particles, colloids and dissolved molecules. Suspended particles, such as sand, vegetable matter and silt range in size from very large particles down to particles with a typical dimension of 10µm. Colloids are very fine particles, typically ranging from 10 nm to 10 µm Dissolved molecules are present as individual molecules or as ions. Most suspended solids smaller than 0.1 mm found in water carry negative electrostatic charges. High turbidity will decrease the amount of sunlight able to penetrate the water, thereby decreasing the photosynthetic rate. When the water is cloudy, sunlight will warm it more efficiently. This occurs because the suspended particles in the water absorb the sunlight, warming the surrounding water. This can lead to other problems associated with increased temperature levels. So in present study researcher tries to assess the waste water temperature of naturally made Nala in Phagwara Tehsil of Punjab and its effect on turbidity. <!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->